Answer:
x-intercept is (13/3, 0)
y-intercept is (0,-13)
Step-by-step explanation:
change y+1 = 3(x-4) into slope-intercept form:
y+1 = 3x-12
y = 3x-13
y-intercept is (0,-13)
to get x-intercept, plug zero in for 'y' and solve for 'x':
0 = 3x-13
13 = 3x
13/3 = x
x-intercept is (13/3, 0)
Answer:
4/pi=w-6/pi
<u>4</u><u> </u><u> </u><u> </u>=<u> </u><u>w</u><u>-</u><u>6</u>
<u>Pi</u><u> </u><u> </u><u> </u><u> </u><u> </u><u>pi</u>
Cross mutiply
Pi(w-6)=4(pi)
Wpi - 6pi =4pi
Collect like terms
Wpi=4pi + 6pi
Wpi =10pi
<u>Divide</u><u> </u><u>both</u><u> </u><u>sides</u><u> </u><u>by</u><u> </u><u>pi</u>
<u>Wpi</u><u> </u>= <u>10pi</u>
Pi pi
W = 10
Answer:
-23
Step-by-step explanation:
We are given the functions;
h(x) = 5x - 3 and j(x) = -2x
Now, we want to find h[j(2)]
j(2) = -2(2)
j(2) = -4
Thus;
h(-4) = 5(-4) - 3
h(-4) = -20 - 3
h(-4) = - 23
Answer:
Ratio 2:3 I think :)
Step-by-step explanation:
Answer:
1/2jdjdjjdjdjdhdhdhdhdhhdhdhdhdhd